Seroprevalence of Dengue virus among pregnant mothers and their-newborn infants in the southwest of Saudi Arabia - Ali S. Alqahtani (IMR Press, 2020)
Dengue virus (DENV) is one of the most serious arthropod-borne viruses. This study was performed to investigate the prevalence of the virus in Najran, a city in the south west of Saudi Arabia. Four hundred and ten paired maternal and umbilical serum samples were obtained from mothers and their newborn infants. The samples were tested for the presence of IgG antibodies by ELISA. Anti-DENV IgG antibodies were detected in 31 maternal samples (7.6%), while all newborn samples were negative. All maternal seropositive samples were negative when tested by PCR. These results are further indication that DENV is endemic in Saudi Arabia and enhanced DENV surveillance is necessary.